PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA MELALUI MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOTION (CIRC) - Rahmi, Yulia; Marnola, Ilham (Jurnal Basicedu, 2020)
The purpose of this study was to describe the improvement in reading comprehension results using CIRC type cooperative learning in class V SDN 04 Padang Ganting. This study uses a qualitative approach to the classroom action research design. The design of this research includes (1) preliminary studies, preparation of action plans, (2) research implementation activities consisting of the stages of implementing actions, observations and reflection stages. This action research was carried out in two cycles. The researcher acts as a presenter / practitioner in the learning process, while the observer is a colleague on duty at the research site. The results showed that the use of the CIRC type cooperative approach in learning to read comprehension was effective for improving reading comprehension skills. This can be seen from the value of students obtained from the first cycle which is an average student score of 7.09, while in the second cycle the average value of students is 8.55. From the results of this study it can be concluded that learning to read comprehension by using a CIRC type cooperative approach can improve student learning outcomes.